Astragalus Polysaccharide Promotes Doxorubicin-Induced Apoptosis by Reducing O-GlcNAcylation in Hepatocellular Carcinoma - Mingzhe Li; Fangfang Duan; Zhiqiang Pan; Xiaomei Liu; Wenli Lu; Chao Liang; Zhaoqin Fang; Peike Peng; Dongwei Jia (Cells, 2023)
The toxicity and side effects of chemotherapeutic drugs remain a crucial obstacle to the clinical treatment of hepatocellular carcinoma (HCC). Identifying combination therapy from Chinese herbs to enhance the sensitivity of tumors to chemotherapeutic drugs is of particular interest. Astragalus polysaccharide (APS), one of the natural active components in Astragalus membranaceus, has been reported to exhibit anti-tumor properties in diverse cancer cell lines. The aim of this study was to determine the effect of APS on Doxorubicin (Dox)-induced apoptosis in HCC and the underlying mechanism. The results showed that APS dose-dependently promoted Dox-induced apoptosis and enhanced endoplasmic reticulum (ER) stress. Additionally, APS decreased the mRNA level and protein stability of O-GlcNAc transferase (OGT), and increased the O-GlcNAcase (OGA) expression. Furthermore, OGT lentiviral transfection or PugNAc (OGA inhibitor) treatment reversed the ER stress and apoptosis induced by the combination of Dox and APS. A xenograft tumor mouse model confirmed that the combination of APS and Dox showed an advantage in inhibiting tumor growth in vivo. These findings suggested that APS promoted Dox-induced apoptosis in HCC cells through reducing the O-GlcNAcylation, which led to the exacerbation of ER stress and activation of apoptotic pathways.